Влияние курсового приема L-орнитин- L-аспартата на фиброз и стеатоз печени у больных ассоциированной с нарушениями метаболизма жировой болезнью печени (неалкогольной жировой болезнью печени), имеющих гипераммониемию - Е. V. Garanina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Introduction. Hyperammonaemia develops both in cirrhosis and earlier fibrotic stages during metabolic-associated fatty liver disease (MAFLD). Besides neurotropic, ammonia exerts the hepatotoxic and profibrotic effects. L-ornithine-L-aspartate (LOLA) has been proved effective in treatment for hyperammonaemia in cirrhosis patients.Aim. An impact study of the LOLA course therapy on inflammation, steatosis and liver fibrosis biomarkers in MAFLD.Materials and methods. A total of 90 patients were divided between two cohorts. The control cohort included patients with liver steatosis S0–S1, absent liver fibrosis, normal liver function tests, clean history of liver disease, while MAFLD cohort gathered liver steatosis S2–S3 and METAVIR fibrosis F1. Steatosis and fibrosis were assessed with a Fibroscan 502 unit with CAP measurement. All patients had ammonia estimated from whole blood. At high ammonia, LOLA was ordered at 9 g/day for 8 weeks, with control of blood ammonia, AST, ALT, GGT, CRP and ferritin, as well as fibrosis and steatosis post-therapy.Results. The study enrolled 45 patients of the MAFLD and 45 — of control cohort. Hyperammonaemia was revealed in 26 (58 %) MAFLD and 3 (7 %) control patients (p <0.001). MAFLD-hyperammonaemic patients also had the significantly higher male ratio, type 2 diabetes and severer hepatic steatosis rates vs. hyperammonaemia-negative MAFLD individuals. In 8 weeks of LOLA therapy, the ALT, AST, GGT, ferritin and CRP levels decreased significantly, and blood ammonia attained normal range (p <0.001). Elastometry liver stiffness decreased in 22 (85 %) patients, reaching F0 values in 6 cases (p <0.001). The steatosis grade reduced in 18 (69 %) individuals.Conclusion. LOLA normalises blood ammonia levels and reduces the severity of inflammation, steatosis and liver fibrosis.